2020
DOI: 10.2147/clep.s259953
|View full text |Cite
|
Sign up to set email alerts
|

<p>Temporal Trends of the Incidence of Ischemic Heart Disease in Iran Over 15 Years: A Comprehensive Report from a Multi-Centric Hospital-Based Registry</p>

Abstract: Background: We sought to explore the temporal trend of ischemic heart disease (IHD) incidence rate (IR) in a large city of Iran. Methods: The study population comprised hospitalized patients who were living in Isfahan, Iran, with first or recurrent IHD during the period of 2001 to 2016. To identify patients, clinical diagnostic codes were applied according to the International Classification of Diseases 10 (ICD-10: I20.0, I21-I25) and the "World Health Organization Monitoring Trends and Determinants in Cardiov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Previous studies revealed that the highest impact attributed to PM 10 , with an attributable proportion of 7.037% (5.02–10.27), corresponding to an excess of 637 (435–890) hospital admission of all CVDs (ICD9: 390–459) in Isfahan, during our study period ( Kermani et al, 2018 ). Moreover, recent estimates indicated that in Isfahan, age-, sex-, and place-of-residence adjusted incidence rate (per 10,000) of ischemic heart disease in Isfahan were 41.23–59.92, based on different reference populations during the period between April 2010 to March 2012 ( Nouri et al, 2020 ). In addition, the prospective studies have highlighted a high incidence of various risk factors, including hypertension, obesity, metabolic syndrome, hypercholesterolemia, diabetes mellitus, hypertriglyceridemia, and smoking in Isfahan ( Sarrafzadegan et al, 2011 ; Sadeghi et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that the highest impact attributed to PM 10 , with an attributable proportion of 7.037% (5.02–10.27), corresponding to an excess of 637 (435–890) hospital admission of all CVDs (ICD9: 390–459) in Isfahan, during our study period ( Kermani et al, 2018 ). Moreover, recent estimates indicated that in Isfahan, age-, sex-, and place-of-residence adjusted incidence rate (per 10,000) of ischemic heart disease in Isfahan were 41.23–59.92, based on different reference populations during the period between April 2010 to March 2012 ( Nouri et al, 2020 ). In addition, the prospective studies have highlighted a high incidence of various risk factors, including hypertension, obesity, metabolic syndrome, hypercholesterolemia, diabetes mellitus, hypertriglyceridemia, and smoking in Isfahan ( Sarrafzadegan et al, 2011 ; Sadeghi et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2011 and 2012, the CVD, IHD, and stroke SMR reached the greatest reduction, respectively. The difference in mortality rates between intervention and control districts may be related to the impact of IHHP on the incidence and the prevalence of coronary artery disease (CAD) risk factors and lifestyle behaviors in both regions [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Since, sustainability of interventional programs requires to be evaluated [22], prior researches have shown that after the program ended in 2007, high number of IHHP interventions were sustainable and incorporated within the health care system and the community [8,23]. In addition, previous studies indicated the decreasing trend of age-, gender-, and place-of-residencestandardized IHD and stroke incidence in the intervention [14,15,24]. The changes in incidence rates could be due to the changes in known coronary risk factors in the population which is likely one of the implications of IHHP implementation [18].…”
Section: Discussionmentioning
confidence: 99%
“…Detailed descriptions of the methods used in this project have been provided in previous reports. [ 19 ]…”
Section: Methodsmentioning
confidence: 99%